Topicals in Skin Rejuvenation: Prescription Topicals - Sherber, Noëlle S. (Facial Plastic Surgery, 2014)
With the recent proliferation of over the counter cosmeceuticals, prescription topical skin treatments have the cache of being evidence-based and not being available outside the setting of a patient–physician interaction. In the setting of facial rejuvenation, patient demand for prescription topical skin treatments falls into three main roles: (1) stimulation of collagen production; (2) improvement of dyspigmentation; and (3) amelioration of adult acne.
Keywords: skin care; retinoids; glycolic acid; hydroquinone; antiaging